Sharing the Land at Moose Factory in 1763 - Long, John; Preston, Richard; Srigley, Katrina; Sutherland, Lorraine (Ontario History)

(untitled) (The Ontario Historical Society, 2017)
In the 18th century the Indigenous peoples of the James Bay region shared land near the coast, a few resources, and furs from a vast hinterland with European newcomers. The Royal Proclamation of 1763 excluded Rupert’s Land – an appropriate decision for it was quite distinct from lands in the south where settlers were acquiring Indigenous land on the fee simple real estate model. What were the James Bay indigenous people’s conditions for sharing their land? It was arguably their principles, and not King George’s edict, that characterized the year 1763 at Moose Fort (Moose Factory). This paper draws on Hudson’s Bay Co. records to examine what was being shared with the newcomers in this northern region. Unlike in the southern regions, the newcomers had no intention of displacing Indigenous peoples. A modest sharing of land and a generous sharing of food and fur resources, on terms congenial to its first inhabitants, characterizes 1763 in this northern region.